Evaluating the benefits and challenges of using authentic materials in EFL context for listening purpose - Alamri, Wafa (Frontiers in Education, 2025)
Learning a second language through listening skills is not an easy task, as learners have to consume content and linguistic knowledge at the same time during listening. Utilization of authentic materials is much more convenient and easier with the advancements of modern communication tools like videos, podcasts, and TED talks, thereby leaving a positive impact on the learner. This study addresses the research gap in using authentic listening materials by focusing on the challenges and benefits associated with authentic materials when used in, English as a Foreign Language (EFL) contexts. A narrative literature review was carried out using articles from various databases such as Scopus, Google Scholar, and ERIC. The findings showed that although authentic materials support motivation and real-life communication, these authentic materials can be uncomfortable to use for reasons of cultural differences, background knowledge, and cognitive load. The study concludes that despite the limitations of authentic materials, these resources can be pedagogically valuable when implemented carefully and considerably.